MathMindset: game-based learning to reduce math anxiety / Farah Nabilah Fairos, Nor Intan Shafini Nasaruddin and Siti Feirusz Ahmad Fesol - Fairos, Farah Nabilah; Nasaruddin, Nor Intan Shafini; Ahmad Fesol, Siti Feirusz (College of Computing, Informatics, and Mathematics, 2024)
Mathematics is one of the most important subjects for students to learn. Understanding topics, concepts, and formulas is crucial to fostering interest in learning it. The problem of anxiety in Mathematics arises when students fear dealing with it due to lack of confidence and interest, stemming from a lack of enjoyment in learning. To address this issue, a beneficial approach for students is through game-based learning. By implementing game-based learning as a platform for education, arithmetic topics can be learned easily without students realizing it. This project has three objectives: to design game-based learning that combines elements to foster interesting and enjoyable learning experiences, to develop game- based learning tools that can help students reduce anxiety related to mathematics, and to assess the effectiveness and enjoyment of game- based learning in reducing math anxiety among elementary school students. The GDLC methodology is utilized in the development of this project due to its suitability for saving time and ensuring a clear and simple development process. Upon completion of the project, results gathered from the 1st grade students of SK Merlimau 2, Merlimau, Melaka, based on a questionnaire using the EGameFlow model, revealed a 96.4% enjoyment rate. Additionally, questionnaires employing MSEAQ have also shown high scores. Thus, MathMindset: Game-Based Learning to Reduce Math Anxiety has successfully achieved all its objectives.